Characteristics Analysis and Intestinal Effects of Probiotic‐Derived Nano‐Selenium by Lactobacillus bulgaricus CICC 20247 - Yebo Wang; Ke Li; Wenting Zhu; Huijuan Xi; Meng Qi; Ping Chen; Hanyu Chen; Chun‐e Zhang; Ying Luo (eFood)
ABSTRACT The bioproduction of selenium nanoparticles (SeNPs) is garnering increasing attention as an environmentally friendly method, given that many microorganisms inherently possess the ability to synthesize nano‐selenium. In the present study, Lactobacillus bulgaricus (L. bulgaricus) was selected to convert sodium selenite to SeNPs, the optimum conversion conditions were finally established, the morphology and structure of SeNPs were characterized as uniform distribution spherical particles with average size of 92.4 nm, in combination with field emission scanning electron microscope (FE‐SEM), transmission electron microscope (TEM), X‐ray photoelectron spectroscopy (XPS), and Fourier transform infrared spectroscopy (FTIR). 16S rDNA sequencing and genomic sequencing revealed that SeNPs influenced the composition of the gut microbiota, the abilities of immune and metabolism in mice were improved significantly after SeNPs supplement. The results corroborated the potential of SeNPs synthesized from probiotic L. bulgaricus CICC 20247 in intestinal health promotion and various biomedical even food processing applications.